The Effect of Reeds and Washed Rice Water on The Growth and Production of White Oyster Mushroom (Pleurotus Ostreatus) - L Limbongan, Yusuf (Riviera Publishing, 2023)
This study aims to determine the effect of reeds as a planting medium and washed rice water on the growth and production of white oyster mushroom. The research was conducted in April-July 2021 in Polopadang, Kapala Pitu District, North Toraja Regency.The research was carried out in the form of a factorial experiment with 2 different factors arranged in a randomized block design (RBD), namely: As the treatment used Imperata and washed rice water. Imperata (reeds) as 1st factor consists of three treatment levels, namely R0 = control, R1 = 10% Reeds, R2 = 20% reeds, while washed rice water as 2nd factor consists of five treatment levels, namely W0 = control, W1 = 10 ml of washed rice water, W2 = 20 ml of washed rice water, W3 = 30 washed rice water, W4 = 40 ml of washed rice water. The results showed that the treatment of 10% Imperata (L1) and 10 ml water leri (L2) gave the best results on the growth and production of white oyster mushrooms in this case, namely: number of mushroom pin head, fresh fruit body weight, and mushroom diameter. Number of pin head and diameter of mushroom hood have a positive and significant correlation to weight of mushroom, each with a correlation coefficient 0.799 and 0.807. This research implies that the use of reeds and rice washing water in the cultivation of white oyster mushrooms has promising potential. This combination can promote mold growth, reduce production costs, and contribute to financial sustainability.